2019
DOI: 10.1002/open.201800228
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Graphene‐Encapsulated Copper Particles by Chemical Vapor Deposition in a Cold Wall Reactor

Abstract: Functional fillers, such as Ag, are commonly employed for effectively improving the thermal or electrical conductivity in polymer composites. However, a disadvantage of such a strategy is that the cost and performance cannot be balanced simultaneously. Therefore, the drive to find a material with both a cost efficient fabrication process and excellent performance attracts intense research interest. In this work, inspired by the core–shell structure, we developed a facile manufacturing method to prepare graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The synthesis of carbon-encapsulated metal nanoparticles can be conducted by several methods, such as chemical vapour deposition and thermal treatment. 21,22 So far, these methods usually need high temperatures and a multi-step process, which includes the synthesis of metal nanoparticles before the coating of carbon layers. Recently, liquid-phase plasma technology, socalled solution plasma (SP), has been reported that it can simply synthesize bimetallic nanoparticles and carbon-doped with heteroatoms under room temperature and pressure condition.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of carbon-encapsulated metal nanoparticles can be conducted by several methods, such as chemical vapour deposition and thermal treatment. 21,22 So far, these methods usually need high temperatures and a multi-step process, which includes the synthesis of metal nanoparticles before the coating of carbon layers. Recently, liquid-phase plasma technology, socalled solution plasma (SP), has been reported that it can simply synthesize bimetallic nanoparticles and carbon-doped with heteroatoms under room temperature and pressure condition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another interesting study was conducted by Chen et al for the first time to encapsulate Cu particles by few layer graphene grown via cold wall CVD [ 92 ]. The synthesis of graphene-encapsulated Cu nanoparticles (GCPs) in their work was inspired by the core–shell structure in order to replace Ag as a functional filler in polymer composites.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…11,12 Nanocarbons such as carbon black, carbon nanotubes, porous and nonporous carbon materials and graphene have shown large specific surface areas, high conductivity, electrocatalytic activity, mechanical capacity, ultra-light characteristics, and chemical and thermal resistance. [13][14][15][16][17][18] Heteroatom (nitrogen, boron, and phosphorus) doped nanocarbon has shown the higher ORR activity. [19][20][21][22][23] Previously, the nanocarbon materials have been successfully synthesized by catalytic or noncatalytic chemical vapor deposition, pyrolysis, electric arc discharge, and direct-current (DC) discharge plasma from various organic solvents.…”
Section: Introductionmentioning
confidence: 99%